2017
DOI: 10.17161/jas.v0i0.5712
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of team-fan role identity on self-reported attendance behavior and future intentions

Abstract: Attendance at college sporting events generates billions of dollars annually for athletics departments at the college level in the United States. Based on Identity Theory and prior research, we developed and tested two models that were successful in predicting actual attendance, attendance intentions (conative loyalty), and support for the team across time. Respondents (N = 165; 60% female, 95% Caucasian) filled out three surveys across the year. In Model A (RMSEA = .066, x 2 /df = 50.02/29 = 1.73), prior seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 32 publications
(43 reference statements)
1
44
0
Order By: Relevance
“…Three items from Trail and James's (2001) team identification index (TII) were used with a seven-point Likert scale (1 = strongly disagree to 7 = strongly agree). The scale of TII is appropriate in the present study as it captures the extent to which one's role of being a fan is important (Trail et al, 2017). Revisit intention was assessed with four items adapted from Song et al (2014) with a seven-point Likert scale (1 = strongly disagree to 7 = strongly agree) (see Appendix B for all items).…”
Section: Study 1 Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three items from Trail and James's (2001) team identification index (TII) were used with a seven-point Likert scale (1 = strongly disagree to 7 = strongly agree). The scale of TII is appropriate in the present study as it captures the extent to which one's role of being a fan is important (Trail et al, 2017). Revisit intention was assessed with four items adapted from Song et al (2014) with a seven-point Likert scale (1 = strongly disagree to 7 = strongly agree) (see Appendix B for all items).…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…Identity theory has its basis in role-identity theory, which indicates that individuals' actions are formed by how they want to perceive themselves and to be perceived by others (Jacobson, 2003). People have role identities that represent their social roles (e.g., being a fan), which are directed by past behaviors and direct future behaviors (Trail, Anderson, & Lee, 2017). Social identity theory, on the other hand, refers to "part of an individual's self-concept which derives from his/her knowledge of his/her membership of a social group (or groups) together with the value and emotional significance attached to that member" (Tajfel, 1981, p. 255).…”
Section: The Moderating Roles Of Team Idmentioning
confidence: 99%
See 1 more Smart Citation
“…When several studies examined the strength or importance of identification (e.g. Dwyer et al , 2013; Shapiro et al , 2013; Trail et al , 2017), Laverie and Arnett (2000) examined several factors influencing sports fans' identity salience, including situation involvement, enduring involvement and attachment, and found that identity salience eventually yielded a positive impact on sports fans' attendance of sporting events. Furthermore, Arnett et al (2003) investigated relationship marketing efforts to engage with university alumni.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerning the variables used as outcomes of the management success of the sports services, satisfaction and future intentions are the most commonly used [16][17][18][19][20]. Among the variables studied to provide these outcomes, we can find service quality [21][22][23][24] and perceived value [25][26][27], together with others, such as emotions [16,28], identity with teams [29,30], or attendance reasons [31,32]. The quality of service is, by far, the most studied and discussed in the literature [33].…”
Section: Introductionmentioning
confidence: 99%